Urgensi Penguatan Identitas Nasional Dalam Menghadapi Society 5.0 Di Era Globalisasi - Zam Zarinah; Rahma Asyifa; Sasmi Nelwati (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
National identity is a very important thing in a country. Without an identity, a country's existence will not be recognized in the eyes of the world. National identity is interpreted as a dynamic condition that is formed from several factors, such as ethnicity, culture, language, religion, ideology, and so on. As time goes by, of course the situation of a country is increasingly changing. Especially in the midst of the era of globalization where all flows of information and culture can be easily accessed. Globalization will not be separated from technological developments which are closely related to the era of society 5.0. In facing society 5.0, in the era of globalization which is marked by technological advances and increasing global interconnection, the need to strengthen national identity becomes increasingly important. The presence of Society 5.0, which emphasizes the integration of technology into all aspects of life, raises new challenges for national identity. In this context, this research aims to explore the urgency of strengthening national identity in facing Society 5.0. This research uses an analytical method by analyzing literature and case studies on strengthening national identity in the context of Society 5.0.